The role of vitamin D in selected autoimmune diseases - review - Dobromiła Osuch; Dominika Opala; Izabela Staszczyk; Aleksandra Drabik; Dominika Szczotka; Antonina Szemplińska; Klaudia Błachnio; Agnieszka Anderska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Vitamin D is a micronutrient whose main role in the human body is to ensure proper calcium-phosphate balance and adequate bone metabolism, having an effect on the immune system, also exhibiting a number of other actions, in particular anti-inflammatory and anti-fibrotic effects, so that its deficiency is reflected in a number of autoimmune diseases. The purpose of this study is to analyze the literature for the role of vitamin D in multiple sclerosis, type 1 diabetes, autoimmune thyroiditis, inflammatory bowel disease and celiac disease. Materials and methods: a thorough analysis of the medical literature available in the PubMed database was performed. Current state of knowledge: The main role of vitamin D in the human body is to ensure calcium and phosphorus homeostasis and, influence adequate bone metabolism. Vitamin D receptors (VDR), are present in many tissues such as brain, prostate, pancreas, breast, colon and immune cells, suggesting that vitamin D also has extra-skeletal functions and a link to autoimmune diseases. Summary: Low serum vitamin D levels may increase the risk of immune diseases such as type 1 diabetes, multiple sclerosis, autoimmune thyroid diseases, celiac disease and inflammatory bowel diseases.